THE USE OF THE BLUM AND KRATVOL TAXONOMY IN THE TEACHING OF SPECIAL DISCIPLINES (Multidisciplinary Journal of Science and Technology, 2025)
This article tells about the work of Kratvol and Blum as a researcher, about the history of the emergence of taxonomies of educational purposes, about samples of verbs, the stages of which correspond to the levels of thinking.